2009
DOI: 10.1111/j.1095-8649.2009.02394.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecological niche specialization inferred from morphological variation and otolith strontium of Arctic charr Salvelinus alpinus L. found within open lake systems of southern Baffin Island, Nunavut, Canada

Abstract: The presence of two morphotypes of Arctic charr Salvelinus alpinus was confirmed via morphological variation and otolith strontium (Sr) within three open-lake systems of southern Baffin Island, Nunavut, Canada: Qinngu (LH001), Iqalugaarjuit Lake (PG082) and Qasigiat (PG015). Analysis of otolith Sr indicates that a component of each S. alpinus population within lakes LH001 and PG082 is migratory (large-maturing S. alpinus), whereas another component is lake-resident (small-maturing S. alpinus). Alternatively, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(63 citation statements)
references
References 96 publications
2
61
0
Order By: Relevance
“…Ovaries of maturing females were preserved for determination of fecundity. Charr that were previously identified as anadromous and lake-resident life-history morphs via strontium and morphological investigation (Loewen et al, 2009) were used in subsequent analyses.…”
Section: Study Area and Field Collection Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ovaries of maturing females were preserved for determination of fecundity. Charr that were previously identified as anadromous and lake-resident life-history morphs via strontium and morphological investigation (Loewen et al, 2009) were used in subsequent analyses.…”
Section: Study Area and Field Collection Methodsmentioning
confidence: 99%
“…Within one Southern Baffin charr population, it was observed that lakeresident fish may likely utilise tidal habitats when the physical geography between the lake and river system facilitates ease of passage into tidal habitats (Loewen et al, 2009). Regardless of tidal habitat use, all lakeresident fish from the three study lakes had morphological characteristics that suggest residency, such as long pectoral and pelvic fin lengths, and larger eye diameter.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Sampling juveniles, however, introduces the potential problem of sampling resident (non-migratory) Arctic char instead of anadromous individuals. Cumberland sound Arctic char systems have been relatively well studied and to date only two systems used in the present study seem to harbour resident populations (QAS and IQ1, Loewen et al 2009). Thus we are reasonably confident that our samples should be composed almost entirely of anadromous juveniles.…”
Section: Sample Collection Dna Extraction and Amplificationmentioning
confidence: 97%